2008
DOI: 10.3171/jns/2008/108/3/0458
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intraarterial verapamil in the treatment of cerebral vasospasm after aneurysmal subarachnoid hemorrhage

Abstract: This study indicates that high-dose intraarterial verapamil may be used to treat cerebral vasospasm without compromising hemodynamic stability or increasing ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 12 publications
1
67
0
6
Order By: Relevance
“…In a study using lower doses of verapamil, Feng et al 7 reported statistically significant decreases in MAP of 3.8 Ϯ 1.0% at 10 minutes after treatment and 1.7 Ϯ 1.1% at 20 minutes after treatment. In a study using higher doses of verapamil than those in the current study, Keuskamp et al 8 reported qualitative transient decreases in heart rate and/or blood pressure in some of their patients lasting, at most, 5 minutes with no episodes of hypotension or new bradycardia. Some of the decreases in MAP were greater than 10 mm Hg, but specific measurements were not given.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In a study using lower doses of verapamil, Feng et al 7 reported statistically significant decreases in MAP of 3.8 Ϯ 1.0% at 10 minutes after treatment and 1.7 Ϯ 1.1% at 20 minutes after treatment. In a study using higher doses of verapamil than those in the current study, Keuskamp et al 8 reported qualitative transient decreases in heart rate and/or blood pressure in some of their patients lasting, at most, 5 minutes with no episodes of hypotension or new bradycardia. Some of the decreases in MAP were greater than 10 mm Hg, but specific measurements were not given.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have reported changes in gross neurologic status in treated patients. [7][8][9][10]17 Those parameters were outside the scope of the current study. In the absence of a control patient population, those data may be of limited value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations